Awareness of tuberculosis in the community: time to rethink strategies - Shankar, Meera; V., Ramasubramanian; Ramakrishnan, Balasubramaniam (International Journal Of Community Medicine And Public Health, 2019)
Background: Tuberculosis is highly prevalent in developing countries like India and several strategies have been implemented by the World Health Organization and Government of India in order to minimize its burden. However, effectiveness of these strategies is best achieved when there is adequate awareness among the general population regarding the cause and spread of the disease. This study was carried out to evaluate the knowledge, attitude and practices regarding tuberculosis among general population. Methods: This cross sectional study was carried out among 500 adults visiting our tertiary care center as patients or attenders for a period of one year between April 2018 and March 2019. A structured interview schedule was used to collect information regarding the knowledge, attitude and practices regarding the cause, spread and management of tuberculosis infection. Results: About 73.6% of the study participants felt that tuberculosis was a genetic disorder, while only 12.4% of them were aware that the infection was transmitted through coughing, etc. Moreover, 18% of the participants believed that the medications for treating tuberculosis could be stopped without the supervision of the health care provider. Conclusions: This study has elicited the prevailing misconception regarding the cause, transmission, treatment and prevention of tuberculosis. It is important for policy makers and public health program implementation experts to develop health literacy campaigns to specifically create awareness among the population, so as to facilitate successful mitigation of the disease.